PROFIL HUTAN PEGUNUNGAN KAMOJANG, JAWA BARAT - , ISORALLA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This purpose of the research was to study natural and disturbed mountain forest profile of Kamojang at 1300-1600 m dpl, West Java. Forest profile was made by Oldeman method, data were collected by quadrat plots size 20m x 20m with 4 times replicated. The result showed natural forest composed by 5 strata, disturbed forest composed by 3-4 strata without first strata. The most abundance trees in first strata were Castanopsis javanica between 2-11 ind/0,16 ha and in second strata were Engelhardia spicata between 5-7 ind/0,16 ha. All these locations study were not found any emergent trees and composed by different vegetation. That was because of selective cutting activity to vegetation that had economic value by outside Kamojang society. The most abundance growthform in natural and disturbed forest were sapling between 15-32 species/0,16 ha in natural forest and 3-23 species/0,16 ha in disturbed forest. The most abundance trees and sapling in natural forest were Villebrunea rubescens between 5-51 ind/0,16 ha. In contrast, most abundance trees in disturbed forest were Altingia excelsa 20 ind/0,16 ha and sapling were Erythtroxylum cuneatum between 1-19 ind/0,16 ha. There were variation presence of trees-seedling in natural forest, the most abundance were Morinda tomentosa between 1-26 ind/0,16 ha. The most abundance trees-seedling in disturbed forest were Dysoxylum parasiticum, Hypobathrum racemosum, Laportea sp., dan Macaranga rhizinoides between 3 ind/0,16 ha in Raksamala rehabilitated forest which growth naturally. Cover of canopy in natural forest were 0,17-0,32 ha/0,16 ha. In contrast, there were 0,02-0,08 ha/0,16 ha in disturbed forest. Nutrients content of soil such as NO3, NH4, PO4, K+, C, and BO in all locations both natural forest and disturbed forest werehigh. Content of nitrate around 10-60 ppm. Natural forest had interlock canopy and quilted layers which good for water conservatories. Both natural and disturbed forest were found invasive species Eupatorium odoratum. Raksamala rehabilitated forest were colonied by Kamojang native species. The limiting factor were the light and human activity.